Mindfulness sebagai Mediator Fear of Missing Out dan Problematic Internet Use pada Penduduk Asli Digital - Devi Jatmika; Vella Fitrisia Agustina (Jurnal Ilmu Perilaku, 2020)
The development of internet technology creates a new need for digital natives in order to stay online. The desire to stay connected due to not to be left behind by trends and information is known as fear of missing out (FoMO), thus individuals getting more involved in problematic internet use (PIU). Mindfulness is believed to influence how the relationship between FoMO and PIU. This research aims to know the role of mindfulness as a mediator of the relationship between FoMO and PIU. The number of research subjects were 286 people with age range 17-25 years old in Jakarta. The research method is quantitative. Data were collected using the FoMO scale questionnaire, Mindful Attention Awareness Scale (MAAS), and Generalized Problematic Internet Use Scale 2 (GPIUS 2). Analysis technique used was path analysis. The results revealed that mindfulness did not perfectly mediate FoMO and PIU. However, the path is in line between the variables, which there is a negative relationship between FoMO and mindfulness, mindfulness negatively related to PIU and FoMO positively coorelated to PIU.